Spectroscopic Characterization and Constitutional and Rotational Isomerism of ClC(O)SCN and ClC(O)NCS - Ramos, Luis A. (2013)
Chlorocarbonylthio- and isothiocyanate (ClC(O)SCN and ClC(O)- NCS) have been isolated and characterized by IR (Ar matrix, gas), Raman (liquid), 13C NMR and UV−visible spectroscopies. Vibrational and quantum chemical studies suggest the presence of the syn and anti conformers (SCN group with respect to the CO bond) in the gas phase for both constitutional isomers. syn-ClC(O)SCN is preferred by ΔH° (anti/syn) = 1.3(0.3) kcal mol−1 . The solid-state structure of ClC(O)SCN has been determined by single crystal X-ray diffraction analysis at low temperature. The crystalline solid consists exclusively of molecules in the syn conformation. On the other hand, the anti form is more stable for the ClC(O)NCS isomer. The structure of ClC(O)NCS and its conformational composition were determined by gas electron diffraction. An unusual low syn → anti interconversion energy barrier of 0.98 (0.15) kcal mol−1 was detected for ClC(O)NCS at cryogenic temperatures. The photochemistry of both constitutional isomers isolated in solid argon at 15 K was studied. Rearrangement of ClC(O)SCN to ClC(O)NCS was observed in the neat liquid and under UV−vis irradiation of ClC(O)SCN isolated in solid argon. Properties have been discussed in terms of the valence electronic structure, including the analysis of the He(I) photoelectron spectrum of ClC(O)SCN